Sujeito e autoria em artigos de opinião de alunos do ensino médio integrado : uma abordagem discursiva - Holanda, Maria Simone da Silva (2013)
It is noticed that, in many schools, the teaching of the Portuguese language still occurs from the standpoint of transparency of language, a content-based approach. Regarding to the students' authority of written productions, it is observed that the designation of the author is often associated with the idea of artistic production, literary or scientific. However, the present work aims to analyze the occurrence of authoring clippings of a corpus of opinion articles, dissertation-argumentative texts produced by integrated high school students of an educational institution. Thus, it is relevant the notion of subject as a discursive position, aiming to understand how the process of taking and/or banning of authorship. Therefore, we used the theoretical Discourse Analysis of French, AD, guided by the Pêcheux s studies. In this theoretical framework, we focused on the conception of subject, authorship, text, discourse, discursive formations, ideology, discursive memory and production conditions. It is noteworthy, according to the specificities of the corpus, the importance of theoretical contributions from authors such as Foucault, Gallo, Indursky, Lagazzi, Orlandi, Pacific, and Pfeiffer Tfouni that also address the question of the subject and the author function. It s intended, in this study, to investigate the possibilities of movement of the subject towards the production of an argumentative text, its insertion in discursive memory as well as historical repeatable, in specific socio-ideological position. In order to getting a better comprehension of it, it is essential to understand the concept of interpretation and meaning, not thought as a mere decoding process, since the language is socio-historical. It must be said that in AD, the interpretation is linked to the subject, the history and ideology. Thus, the interpretation leads to authorship, since it works to interdiscourse. The sense, in turn, occurs through gestures of interpretation, from the position of subject in a given discursive formation. Thereby, it is important to understand that the methodology adopted in this work is based on a qualitative approach, focused on the analyses clippings opinion articles, considering in them the intrinsic tension between paraphrase and polysemy, the presence of linguistic marks as well as ideological heterogeneity in the discursive operation that point authorship marks, the forms of repetition of meaning in the text, the inscription of the subject in a specific socio-ideological position. In this approach, AD provides theoretical device that allows the analyst to identify such elements, assuming that the subject may, or not, occupy the position of the author of his speech. Based on these considerations, it is worth realize that the results achieved regarding to the subject and written opinion articles show that there was exercise of author function, even though many of the students could not take this discursive position in his work with the argument text in the context of school, since the activities of reading and writing are still restricted to the school speech, which is implicit the imposition of standard models and formal repetition and, therefore, the subject just reproduces the speech, not historicizes it in a interpretable way, as consider Orlandi.